An APSES Transcription Factor Xbp1 Is Required for Sclerotial Development, Appressoria Formation, and Pathogenicity in Ciboria shiraiana - Zhang, Shuai; Zhu, Panpan; Cao, Boning; Ma, Shuyu; Li, Ruolan; Wang, Xie; Zhao, Aichun (Frontiers in Microbiology, 2021)
Sclerotinia diseases are important plant fungal diseases that, causes huge economic worldwide losses every year. Ciboria shiraiana is the main pathogen that results in mulberry sclerotia diseases. Sclerotia and appressoria play important roles in long-term pathogen survival and in host infection during life and disease cycles. However, the molecular mechanisms of sclerotial development and appressoria formation in C. shiraiana have not been well studied. Here, an APSES-type transcription factor in C. shiraiana, CsXbp1, involved in sclerotial development and appressoria formation was functionally characterized. Bioinformatics analyses showed that CsXbp1 contained an APSES-type DNA binding domain. The expression levels of CsXbp1 were higher in sclerotia and during later stages of infection. Compared with wild-type strains, hyphal growth was slower, the number and weight of sclerotia were reduced significantly, and appressoria formation was obviously delayed in CsXbp1 RNAi strains. Moreover, the CsXbp1 RNAi strains showed weakened pathogenicity owing to compound appressoria defects. Tobacco rattle virus-mediated host‐induced gene silencing enabled Nicotiana benthamiana to increase its resistance to C. shiraiana by reducing the CsXbp1 transcripts level. Thus, CsXbp1 plays vital roles in sclerotial formation, appressoria formation and pathogenicity in C. shiraiana. This study provids new insights into the infection mechanisms of C. shiraiana and plant resistance breeding.